Catalytic Toluene Reforming with In Situ CO2 Capture via an Iron–Calcium Hybrid Absorbent for Promoted Hydrogen Production. Issue 6 (17th April 2020) - Han, Long; Liu, Qi; Zhang, Yuan; Wang, Qinhui; Rong, Nai; Liang, Xiaorui; Feng, Yi; Ma, Kaili; Yan, Mi; Hu, Yanjun
Abstract : A two‐step sol–gel method is adopted to prepare an iron–calcium hybrid absorbent (Ca–Al–Fe) integrating iron catalysis component and inert support with CaO for calcium looping gasification. Effects of Ca–Al–Fe on cyclic CO2 capture reactivity, mechanical strength, and enhanced reforming of biomass tar model component (toluene) are investigated by comparing with three reference absorbents. Results show that main components of Ca–Al–Fe are CaO, mayenite (Ca12 Al14 O33 ), and brownmillerite (Ca2 Fe2 O5 ). Ca12 Al14 O33 plays key roles in keeping stable cyclic carbonation reactivity and significantly promotes mechanical strength of the novel absorbent. In comparison with other absorbents without coupling Ca12 Al14 O33 or Ca2 Fe2 O5, Ca–Al–Fe approaches the highest toluene conversion (around 60%) and has the lowest coke deposition (12.2 mg g −1 ), due to the synergetic influences of Ca2 Fe2 O5 and Ca12 Al14 O33, which significantly promotes hydrogen production while reducing CO2 yield in reforming syngas. In addition, influences of reaction conditions such as iron loading, reaction temperature, molar ratio of H2 O to carbon in toluene, and absorbent particle size on toluene reforming are examined in the presence of Ca–Al–Fe. Potential reaction routes of toluene reforming are also analyzed and discussed. Abstract : A CaO‐based iron–calcium hybrid absorbent is synthesized by a modified sol–gel method for biomass calcium looping gasification. Due to synergetic effects of mayenite and brownmillerite, this absorbent presents stable cyclic carbonation reactivity, high mechanical strength as well as maximum toluene conversion and hydrogen yield due to improved absorbent structure, catalytic tar reforming, and enhanced water gas shift reaction.